It's Not Just about Bicycle Riding: Sensory-Motor, Social and Emotional Benefits for Children with and without Developmental Disabilities - Sarah A. Schoen; Vincentia Ferrari; Andrea Valdez (MDPI AG, 2022)
Background: A developing area for therapy is teaching children to ride a bicycle. Little has been written about the effectiveness of these programs. This study explored outcomes from participation in a novel bicycle riding program for children with a wide array of developmental challenges. Method: Two studies were conducted; a nonconcurrent, multiple baseline design with four participants and a pretest-posttest single group with 15 children. Results: Study 1 participants improved on broad jump. Balance positions showed variable responses. Study 2 participants showed significant improvement on broad jump, and a trend toward significance walking forwards and backwards. Parents reported improvement in following rules, participating in daily routines, interacting with peers, and feeling good about him/herself and a change in child's participation in community and extracurricular activities. All children improved in glide time or achieved independent riding. Conclusions: Preliminary evidence was found for the effectiveness of one approach for developing motor and social skills within the context of learning to ride a bicycle. Children over the age of 6 years were able to ride a two-wheeled bicycle at the end of the program. Participation suggested improvement in motor coordination and dynamic balance as well as changes in measures of social interaction and self-esteem.